The Role of Pesantren Kilat in Enriching Life Skills, Creativity, and Religious Students of Al Kautsar Yogyakarta - M.Wagio (Insight School Academy, 2023)
Introduction to The Problem: The negative impacts of modern development have led individuals into three interrelated conditions: limited life skills, low creativity, and moral degradation resulting from weakened religiosity. These conditions need to be addressed through education starting from early childhood. Purpose: Therefore, this study aims to respond to these challenges by describing a non-formal educational program known as a “one-night pesantren” (pesantren semalam) conducted at a madrasah by the Al Kautsar Foundation, Yogyakarta. Design/methods/approach: This research employs a qualitative design with a descriptive approach. Data were collected through documentation to examine the program concept based on the event structure, observation to understand its practical implementation in the field, and interviews. The respondents included a teacher who also serves as the sixth-grade homeroom teacher, Mrs. Wildi; the program coordinator, Mr. Fani; and the activity supervisor, Mrs. Iin. Findings: The collected data reveal several overarching themes within the program’s activities, particularly efforts to address community issues related to moral development, as well as the provision of essential life competencies for children through the cultivation of creativity. The findings indicate that the “one-night pesantren” program at the madrasah comprises a series of activities that contribute to the enrichment of students’ life skills, creativity, and religiosity, including: (1) ecoprint training activities, (2) reflective film reviews with moral insights, and (3) habituation of worship practices through reading, memorization, and practical application.